Identity and the Collective Mind in Digital Communities: A Socio-Psychological Exploration of Digital Self Formation and Cognitive Transformations - عباس, زلزلة محمود (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This study explores the psychological and cognitive transformations of the self and identity formation within digital societies. Drawing from social psychology, it employs theoretical frameworks such as Goffman’s dramaturgical model, Mead’s symbolic interactionism, and Tajfel’s social identity theory to understand how digital identities are shaped and redefined within networked interactions. Findings reveal that digital identity has become a fluid construct influenced by online interactions, social validation, and algorithmic systems. The research highlights how digital collective consciousness can result in both identification with online groups and psychological fragmentation. Emotional contagion, filter bubbles, and the lack of critical engagement contribute to anxiety, social comparison, and alienation. Focusing on the Iraqi context, the study shows that fragile digital literacy and socio-political fragmentation intensify the psychological consequences of digital immersion. The study concludes by recommending educational and psychological strategies to mitigate the negative effects of digital collective influence and foster conscious digital identity development.